Relationship between Teacher Counsellors’ Hours of Exposure to Training in Guidance and Counselling and Professionalism in Service Delivery in Public Secondary Schools in Nairobi, Kenya - Kuria, M.W.G; Muola, J.M; Kithuka, M; Mwania, J.M (International Journal of Contemporary applied sciences, 2015)
Guidance and counselling has been recommended and popularized by the government through the Ministry of Education, Science and Technology. Different Government of Kenya (GoK) reports have made recommendations aimed at enhancing guidance and counselling. In 1971 the Ministry of Education established a Guidance and Counselling section at the ministry headquarters. Teacher counsellors are trained in different institutions such as, public and private universities, middle level colleges and religious organizations. Each institution develops its own curriculum. Some schools provide in-service training for their teacher counsellors while others do not. This results in differences in hours of exposure to training in guidance and counselling contents. The relationship between the teacher counsellors’ hours of exposure to training in guidance and counselling and professionalism in guidance and counselling has not been investigated. The purpose of this study was to find out the relationship between hours of teacher counsellors exposure to training in guidance and counselling and professionalism in the provision of services in secondary schools. The study involved a sample of 25% of the accessible population from randomly selected secondary schools in Nairobi County in Kenya. The researcher used the ex-post facto research design. A questionnaire was used to collect data from teacher counsellors. A guidance and counselling room observation checklist was completed by the Head of Department (HOD) guidance and counselling. Statistical Package for Social Sciences (SPSS) version 17.0 was used to analyse the data descriptively. To test the null hypotheses, Pearson’s Product Moment Correlation coefficient (r) was used at 5% alpha level. A significant positive relationships between number of hours of exposure and (a) application of counselling skills and techniques, (b) management of counselling resources and (c) observation of ethics (r = 0.702, 0.813 and 0.342 respectively) was reported. It was recommended that there was need to have teachers who are adequately trained in the management of resources, application of counselling skills, and observation of counselling ethics in guidance and counselling
Keywords: Guidance; counselling; Professionalism.; Hours of training